Secure SDN Framework for Data Exfiltration via Video Steganography (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
The popularity of steganography in the data exfiltration of private corporate sensitive data is increased. So it is important to detect such malicious activity. Becausethe data being transferred can hide the large amount of data in video becoming increasingly attractive. To ensure privacy and security we proposed an effective steganalysis method to detect hidden data in video by using the SDN framework policy. The main objective of this paper is to prevent the illegal data transmission from the compromised private network by the malicious users.